STUDY ON RICE PRODUCTION ENHANCEMENT IN BANDUNG DISTRICT - Arumsari, Nuraeni; Tasrif, Muhammad (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
Agricultural enterprises have a very high dependence on land. If the availability of agricultural land is threatened, the agricultural products are threatened. The development of a region also requires land, but sometimes due to land constraints, there is a lot of conversion of agricultural land, including rice fields that ultimately impact on rice production. Bandung Regency is one of the areas that cannot be separated from the problem of development and conversion of agricultural land, meanwhile Bandung Regency is one of the contributors to the availability of food crops, one of them is rice. The government's target to be self-sufficient in food and make Indonesia as the world's food granary in 100 years of Indonesia's independence makes Bandung Regency must join efforts to increase rice production in the midst of widespread land use. This research was conducted to model the dynamics of rice production in Bandung regency. The approach used is system dynamics methodology that can contribute in understanding a problem built through dynamic hypothesis. Through the system dynamics method, a model developed illustrating the increase in rice production by identifying the various related elements and patterns of interrelationships between them. With the help of the model, several policy scenarios can be designed to increase rice production. The results showed that rice production if not intervened by policy, the rate of growth will decrease, especially if the over of fixed land functions still occur. The policy of using new varieties, namely INPARI 42 with a delay time of 3 years implementation, coupled with pest prevention policies, availibility and affordability fertilizers, and irrigation improvement can encourage the growth rate of rice production in Bandung Regency.